SINTESIS SILIKA MCM-41 DAN UJI KAPASITAS ADSORPSI TERHADAP METILEN BIRU - Mustofa Ahda; Sutarno Sutarno; Eko Sri Kunarti (Universitas Ahmad Dahlan, 2013)
Synthesis of MCM-41 with hydrothermal time variation 18, 24, 36, 48 hours using templating agent cetiltrimetilammonium bromide (CTAB) has been done. The results showed that the time of hydrothermal influence the intensity and the index field (ao). Synthesis of MCM-41 with a time of hydrothermal 24 hours produce the highest intensity which indicates that MCM-41 has the best crystallinity. While testing the adsorption capacity of MCM-41 has 37,037 mg/g for adsorption of the methylene blue.